2021
DOI: 10.1002/jdn.10079
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dentate gyrus in adult mice exposed to acetaminophen (paracetamol) on postnatal day 10

Abstract: Acetaminophen (AAP; or paracetamol) is a widely used nonprescription drug with antipyretic and analgesic properties. Alarmingly, there is an increasing body of evidence showing that developmental exposure to AAP is associated with adverse behavioural outcomes later in life. We have previously shown that relevant doses of AAP in 10‐day‐old mice affected memory, learning and locomotor activity in the adult animals. Interestingly, the neurons of the dentate gyrus (DG) have a relatively late time of origin as they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…It is well documented that the first 2 weeks after birth in mice, equivalent to the period from the last trimester of pregnancy to the first few years after birth in humans, is the critical period for DG development [ 164 ]. It has been indicated that early postnatal treatment potentially repairs the structure, which is associated with continuous symptom alleviation [ 165 ].…”
Section: Hippocampal Neurogenesis-based Regenerative Therapy Proposed...mentioning
confidence: 99%
“…It is well documented that the first 2 weeks after birth in mice, equivalent to the period from the last trimester of pregnancy to the first few years after birth in humans, is the critical period for DG development [ 164 ]. It has been indicated that early postnatal treatment potentially repairs the structure, which is associated with continuous symptom alleviation [ 165 ].…”
Section: Hippocampal Neurogenesis-based Regenerative Therapy Proposed...mentioning
confidence: 99%
“…A large body of evidence suggests the role of APAP overdose in neurodevelopmental impairment [15][16][17]. Nevertheless, few studies relate adult neurogenesis to paracetamol overdose toxicity.…”
Section: Introductionmentioning
confidence: 99%